PENGGUNAAN SLIDE INTERAKTIF PADA PEMBELAJARAN DARING MATERI SUBSTANSI GENETIK UNTUK MENINGKATKAN ASPEK KOGNITIF SISWA - Anggitalina Pramilia Dewi (PGSD Universitas Muria Kudus, 2021)
This research aims to determine the cognitive aspects enhancement of genetic substance material using interactive slide media in the online learning for students of Trensains Muhammadiyah high school grade twelveThis research is a classroom action research conducted in three cycles. Each cycles consist of four stages, they are; planning, implementing, observing, and reflecting. The subject in this research was a twelve grade students of Trensains Muhammadiyah high school sragen in academic year 2020/2021 with the amount 24 students. The data is processed through observation, questionnaire and test. The data analysis was conducted in a descriptive qualitative manner based on the results of observations and questionnaire as well as qualitatively on the result of cognitive test.. The result of the research shows that the number of students who achieved the minimum completeness score (KKM) 70 in the first cycle is 14 students (58,33%), second cycle is 15 students (62,5%), and third cycle is 18 students (75%) from the subject amount 24 24 students. Students cognitive ability increase in each cycle. The average of student cognitive aspect in cycle 1 is 73,3%, cycle 2 is 76,7%, and cycle 3 is 80,4%. Based on the research, it can be concluded that the use of interactive slide media in the online learning of genetic substance material can improve cognitive aspects of student in grade XII MIPA 3 Trensians Muhammadiyah high school Sragen.